2005
DOI: 10.4103/1319-3767.33320
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of colorectal cancer at two hospitals in the western region of Saudi Arabia

Abstract: Patients and Methods: Data of all patients with CRC treated at two hospitals in the Western region of the Kingdom of Saudi Arabia (KSA), between 1993 and 2002, were collected and analyzed. Results: Out of the 121 patients evaluated, ten were excluded because of incomplete data. Out of 111 patients, 59 (53.2%) were males, with a male to female ratio of 1.13: 1 and 49 (44.1 %) were Saudis. Thirty-three patients (29.7%) were 40 years or less and 78 (70.3%) were more than 40 years. Colon cancer was found in 69 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
5
6
0
Order By: Relevance
“…In this study males were more than females but the ratio was almost similar (1: 1.02) which can be compared to that shown by Verschueren RC et al 24 and other studies 10,25,26 . On the other hand Guraya S Y showed a different male to female ratio of (4: 1) Tumor grade pattern in our study was mainly well differentiated adenocarcinoma (45%) then poorly differentiated (26.67%), in a similar study in Saudi Arabia 25 moderately differentiated was the most common followed by poorly differentiated adenocarcinoma.…”
Section: Resultssupporting
confidence: 89%
“…In this study males were more than females but the ratio was almost similar (1: 1.02) which can be compared to that shown by Verschueren RC et al 24 and other studies 10,25,26 . On the other hand Guraya S Y showed a different male to female ratio of (4: 1) Tumor grade pattern in our study was mainly well differentiated adenocarcinoma (45%) then poorly differentiated (26.67%), in a similar study in Saudi Arabia 25 moderately differentiated was the most common followed by poorly differentiated adenocarcinoma.…”
Section: Resultssupporting
confidence: 89%
“…This finding concurs with a data analysis of 111 patients with CRC performed between 1993 and 2002 from two hospitals in the western region of KSA (Ministry of Health K, 2007) The authors reported that the mean age at diagnosis was 59 years in males and 56 years in females. In our study cohort, the incidence of CRC was higher in males than females, which is not only in line with reports from KSA but is also consistent with reports worldwide (Al-Ahwal, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…The location of the disease in the colorectal area and its clinical features are also not very different from what has been described in the past (Isbister, 1992;2000;Mansoor, 2002;Al-Ahwal, 2005;Abdul, 2011).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Unfortunately, it is difficult to make relevant comparisons with most studies conducted in the Kingdom because the majority of the few studies that were conducted are hospital-based (AlRadi et al, 2000;Isbister et al, 2000;Ayyub et al, 2002;Al-Ahwal and Al-Ghamdi, 2005;Sibiani et al, 2011) and therefore do not reflect the trend of the disease among Saudis in the Kingdom. However, this striking trend does mirror similar recent reports from other countries Matsuda al., 2010;Matsuda et al, 2011).…”
Section: Discussionmentioning
confidence: 99%